Dangerous pregnancies : mothers, disabilities, and abortion in modern America - Reagan, Leslie J. (ACLS Humanities E-Book., 2010)
Dangerous Pregnancies tells the largely forgotten story of the German measles epidemic of the early 1960s and how it created national anxiety about dying, disabled, and "dangerous" babies. This epidemic would ultimately transform abortion politics, produce new science, and help build two of the most enduring social movements of the late twentieth century--the reproductive rights and the disability rights movements. At most a minor rash and fever for women, German measles (also known as rubella), if contracted during pregnancy, could result in miscarriages, infant deaths, and serious birth defe.